By the Honourable John Nanfan, Esq ; His Majesties lieut. governour and commander in chief in and over the province of New-York, and territories depending thereon in America, and vice admiral of the same. A proclamation : Whereas by and with the advice of Majesties Council for this province, a proclamation issued on the five and tentieth day of January last past ... Given at Fort William Henry in New-York, this 10th day of March, 1701 . (LLMC-digital (Series), 1701)
Offering amnesty to Rip Van Dam, author of libelous tracts, if he turns himself in to the authorities.